2001
DOI: 10.1177/000348940111000914
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Cochlear Implants in Humans

Abstract: The insertion of an intrascalar electrode array during cochlear implantation causes immediate damage to the inner ear and may result in delayed onset of additional damage that may interfere with neuronal stimulation. To date, there have been reports on fewer than 50 temporal bone specimens from patients who had undergone implantation during life. The majority of these were single-channel implants, whereas the majority of implants inserted today are multichannel systems. This report presents the histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
221
2
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(243 citation statements)
references
References 26 publications
13
221
2
7
Order By: Relevance
“…The relationship between the benefits of cochlear implants and the site of hearing impairment varies both with the type of hearing disorder (sensorineural vs. AN) and the specific site of dysfunction. In "sensorineural deafness" the benefits of cochlear implants are unrelated to the numbers of surviving ganglion cells found at post mortem in temporal bone (Fayad et al, 1991;Nadol et al, 2001). In AN, cochlear implants benefit patients with OTOF mutations affecting pre-synaptic release of neurotransmitter from inner hair cell ribbon synapses (Rodriquez-Ballesteros et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the benefits of cochlear implants and the site of hearing impairment varies both with the type of hearing disorder (sensorineural vs. AN) and the specific site of dysfunction. In "sensorineural deafness" the benefits of cochlear implants are unrelated to the numbers of surviving ganglion cells found at post mortem in temporal bone (Fayad et al, 1991;Nadol et al, 2001). In AN, cochlear implants benefit patients with OTOF mutations affecting pre-synaptic release of neurotransmitter from inner hair cell ribbon synapses (Rodriquez-Ballesteros et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of sensory deprivation for long periods, which adversely affects connections between and among neurons in the central auditory system (Shepherd and Hardie, 2001) and may allow encroachment by other sensory inputs of cortical areas normally devoted to auditory processing (i.e., cross-modal plasticity; see Lee et al, 2001;Bavelier and Neville, 2002). Although one might think that differences in nerve survival at the periphery could explain the variability, either a negative correlation or no relationship has been found between the number of surviving ganglion cells and prior word recognition scores, for deceased implant patients who in life had agreed to donate their temporal bones for post-mortem histological studies (Blamey, 1997;Nadol et al, 2001;Khan et al, 2005;Fayad and Linthicum, 2006). In some cases, survival of the ganglion cells was far shy of the normal complement, and yet these same patients achieved high scores in speech reception tests.…”
Section: Likely Limitations Imposed By Impairments In Auditory Pathwamentioning
confidence: 99%
“…Latency differences found in this study are in agreement with the hypothesis of more central excitation by the anodic phase but in disagreement with the higher sensitivity to the cathodic phase found in the cat. Several studies have shown that deafened ears suffer from partial to complete degeneration of the peripheral process (Fayad and Linthicum 2006;Hinojosa and Marion 1983;McFadden et al 2004;Nadol 1997;Nadol et al 2001;Shepherd and Hardie 2001;Zhou et al 1995). Rattay et al's (2001) model indicated that human AN fibers with degenerated peripheral processes were more sensitive to the anodic than to the cathodic polarity and that an anodic phase excited the AN fibers at the central axon.…”
Section: Polarity and Excitation Sitementioning
confidence: 99%